2010
DOI: 10.3141/2181-09
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Flow Number Predictive Model

Abstract: The NCHRP 9-19 panel recommended the repeated load permanent deformation test as a laboratory procedure that could be used to evaluate the resistance of a hot-mix asphalt (HMA) to tertiary flow. No standard test protocol addresses the required laboratory stress to be applied. The test can take several hours until tertiary flow is reached and in many cases the sample may never fail. A model capable of predicting or providing general guidance on the flow number characteristics of a mix can be of great value. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…The results of flow number tests from five mixes are shown in Figure 5, which indicates the flow point of each mix (17). Notable differences in flow behavior are found among the mixes.…”
Section: Deformation Performance Of Rap and Rejuvenator Mixesmentioning
confidence: 97%
“…The results of flow number tests from five mixes are shown in Figure 5, which indicates the flow point of each mix (17). Notable differences in flow behavior are found among the mixes.…”
Section: Deformation Performance Of Rap and Rejuvenator Mixesmentioning
confidence: 97%
“…In 2010, Rodezno (46) further modified this model based on a larger database, to tailor the changes in the environment selected. The finalized model, that is also going to be used in this study is the following: For the purpose of this study, the loading frequency is taken to be equivalent to 18 Hz.…”
Section: Effective Temperature Concept and Modelmentioning
confidence: 99%
“…In 2010, Rodezno (46) developed a predictive Flow Number model. A large database was generated and put together in order to make the model as comprehensive as possible, under different stress levels, temperature combinations, gradations and binder types.…”
Section: The Flow Number Predictive Modelmentioning
confidence: 99%
“…The effects of different mix factors on the flow number have also been studied by different researchers [3][4][5][6]. Kaloush [3] determined that the flow number increases with the viscosity of binder and decreases with the test temperature, effective binder content, and air voids.…”
Section: Traffic Level Million Equivalent Single Axle Load (Esal 80mentioning
confidence: 99%
“…Christensen [5] applied various statistical techniques to relate the flow number with the applied stress level and observed that the flow number decreases with increasing applied deviator stress. Rodezno et al [6] determined that the flow number increases with the viscosity of the binder; however, it decreases with the test temperature and air voids and is affected by aggregate gradation. The current study was not intended to investigate the viscosity of the binder or the test temperature.…”
Section: Traffic Level Million Equivalent Single Axle Load (Esal 80mentioning
confidence: 99%